Pedagogical aspects of preparing future educators for professional activity in the preschool education system - (PhD) Ashurova Oygul Anvarjonovna; Khatamova Zukhrakhon Shavkatjon kizi (Genius Journals, 2025)
The article examines the pedagogical conditions for preparing future educators for the professional and pedagogical process in the preschool education system. The article covers the issues of forming the professional mobility of future educators, increasing their interest in self-education, and using modern educational technologies.
Keywords: preschool education; future educator-teachers; professional activity